Digital Tools and methods to Enhance Learning: The Digitools Project - Gonçalves, Maria José Angélico (2023)
The use of distance education using digital tools in higher education has increased over the last decade, particularly during the COVID-19 pandemic. COVID-19 has resulted in schools shutting down all across the world. This paper aims to present a brief summary of the Digitools Project and a multicultural analysis of the use of e-learning during Covid-19 in six countries. The methodology used was a survey by questionnaire involving teachers, librarians and students. The analysis of the questionnaire results allowed us to identify which dimensions to assess the sustainability of eLearning namely the organizational, socio-cultural and technological context. It also made it possible to assess the perceived usefulness, perceived ease of use, intention to use, actual use and perceived satisfaction. Furthermore, personal, technological and organizational dimensions are also valued for e-learning usage. After reviewing the state of the art, there was a need to define a strategic training plan for the acquisition of basic and advanced skills for eLearning’s implementation and usage.